Peningkatan Kreativitas Anak Di Panti Asuhan Bala Keselamatan (Salvation Army) Dengan Menggunakan Metode Casework - Joice Margaretha Zebua; Malida Putri; Fajar Utama Ritonga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to improve the children's creativity at the Salvation Army Orphanage by using casework procedures. One tactic to stress problem solutions through organized and systematic social interventions is the casework technique. Children who took part in the program shown gains in their ability to think creatively, express themselves, and solve problems. Youngsters who had a natural desire to work and greater self-confidence also benefited. This journal's goal is to foster the imaginations and inventiveness of the kids at the Salvation Army Orphanage through the application of casework techniques, which span the engagement, intake, contract, assessment, planning, intervention, monitoring, evaluation, and termination phases.